Inheritance of Yield Components and Morphological Traits in Avocado cv. Hass From “Criollo” “Elite Trees” via Half-Sib Seedling Rootstocks - Cañas-Gutiérrez, Gloria Patricia; Sepulveda-Ortega, Stella; López-Hernández, Felipe; Navas-Arboleda, Alejandro A.; Cortés, Andrés J. (Frontiers in Plant Science, 2022)
Grafting induces precocity and maintains clonal integrity in fruit tree crops. The complex rootstock × scion interaction often precludes understanding how the tree phenotype is shaped, limiting the potential to select optimum rootstocks. Therefore, it is necessary to assess how elite ‘plus trees’ inherit trait variation to their seedling progenies, and whether such family superiority may be transferred after grafting to the clonal scion. In order to bridge this gap, we quantified additive genetic parameters (i.e., narrow sense heritability – h2, and genetic-estimated breeding values – GEBVs) across landraces, “criollo”, ‘plus trees’ , and their OP half-sib seedling families. We used a G-BLUP model to merge phenotypic characterization of 17 morpho-agronomic traits with genetic screening of 13 highly polymorphic SSR markers in a diverse panel of 104 avocado “criollo” ‘plus trees’. Estimated additive genetic parameters were validated at a five years old common garden trial (i.e., provenance test), in which 22 OP half-sib seedlings from 82 elite ‘plus trees’ served as rootstocks for the cv. Hass clone. Heritability (h2) scores in the “criollo” ‘plus trees’ ranged from 0.28 to 0.51. The highest h2 values were observed for ribbed petiole and adaxial veins with 0.47 (CI 95% 0,2 – 0.8) and 0.51 (CI 0.2 – 0.8), respectively. The h2 scores for the agronomic traits ranged from 0.34 (CI 0.2 – 0.6) to 0.39 (CI 0.2 – 0.6) for weight seed and fruit and total volume, respectively. When inspecting yield variation across five years old grafted avocado cv. Hass trees with elite OP half-sib seedling rootstocks, the traits total number of fruits and fruits’ weight respectively exhibited h2 scores of 0.36 (± 0.23) and 0.11 (± 0.09). Our results indicate that elite “criollo” ‘plus trees’ may serve as promissory donors of seedling rootstocks for avocado cv. Hass due to the inheritance of their outstanding trait values. This reinforces the feasibility to leverage natural variation from ‘plus trees’ via OP half-sib seedling rootstock families. Ultimately, by jointly estimating half-sib family effects and rootstock-mediated heritability, this study promises boosting seedling rootstock breeding programs, while better discerning the consequences of grafting in fruit tree crops.